Adubação da soja em solos sob vegetação de cerrado na região do Triângulo Mineiro - Braga, José Mário; Defelipo, Braz Vitor; de Andrade, Dalton (Revista Ceres, 2025)
The response of soybeans to the application of nitrogen (without inoculation of the seeds), phosphorus and potassium was studied in oxisoil from Minas Triangle with and without the application of limestone,